2020
DOI: 10.3389/fpsyt.2020.00188
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Comorbidity Between Bipolar Spectrum and Obsessive-Compulsive Disorder in an Italian Community Survey

Abstract: Background: The impact of the comorbidity between Obsessive-Compulsive Disorder (OCD) and Bipolar Disorder Spectrum (BDS) remains to be clarified. The objective of this study was to examine the lifetime prevalence of OCD, the strength of the association of OCD with comorbid BDS and the role of comorbidity of OCD with BDS in the impairment of health-related quality of life (HRQoL) in an Italian community survey. Methods: The study is a community survey. The sample (N = 2,267; women: 55.3%) was randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…This data supports the hypothesis that MDQ positivity, by itself, identifies a condition of clinical interest regardless of comorbidity with other disorders. The dimensions explored by the SF-12 (albeit from a subjective perspective) include physical health and functioning, physical pain, vitality, social functioning, emotional condition, and 18 29.5 ± 7.3 7.0 ± 3.5 (N = 201) df 1,238 F = 9.937 p = 0.002 Wilson's disease 19 33.8 ± 9.0 4.4 ± 1.7 (N = 23) df 1,60 F = 0.344 p < 0.568 Carotid atheriosclerosis 20 30.6 ± 8.1 6.2 ± 5.0 (N = 46) df 1,83 F = 1.040 p = 0.311 Major depressive disorder 21 33.8 ± 9.2 5.6 ± 3.6 (N = 37) df 1,73 F = 2.66 p = 0.608 Eating disorders 15 34.0 ± 6.2 4.4 ± 6.6 (N = 60) df 1,97 F = 10.272 p = 0.603 Panic disorders 27 35.5 ± 4.6 2.9 ± 0.9 (N = 123) df 1,160 F = 19.454 p < 0.0001 Obsessive compulsive disorder 22 35.4 ± 6.9 2.9 ± 6.0 (N = 88) df 1,125 F = 3.709 p = 0.056 Post-traumatic stress disorder 23 36.3 ± 6.1 3.9 ± 1.0 (N = 26) df 1,91 F = 1.388 p = 0.243 Simple phobia 28 35.8 ± 6.1 2.5 ± 2.4 (N = 54) df 1,66 F = 10.016 p = 0.002 Agoraphobia 24 35. psychosocial disability. Therefore, these elements are not negligible on a clinical level.…”
Section: Discussionmentioning
confidence: 99%
“…This data supports the hypothesis that MDQ positivity, by itself, identifies a condition of clinical interest regardless of comorbidity with other disorders. The dimensions explored by the SF-12 (albeit from a subjective perspective) include physical health and functioning, physical pain, vitality, social functioning, emotional condition, and 18 29.5 ± 7.3 7.0 ± 3.5 (N = 201) df 1,238 F = 9.937 p = 0.002 Wilson's disease 19 33.8 ± 9.0 4.4 ± 1.7 (N = 23) df 1,60 F = 0.344 p < 0.568 Carotid atheriosclerosis 20 30.6 ± 8.1 6.2 ± 5.0 (N = 46) df 1,83 F = 1.040 p = 0.311 Major depressive disorder 21 33.8 ± 9.2 5.6 ± 3.6 (N = 37) df 1,73 F = 2.66 p = 0.608 Eating disorders 15 34.0 ± 6.2 4.4 ± 6.6 (N = 60) df 1,97 F = 10.272 p = 0.603 Panic disorders 27 35.5 ± 4.6 2.9 ± 0.9 (N = 123) df 1,160 F = 19.454 p < 0.0001 Obsessive compulsive disorder 22 35.4 ± 6.9 2.9 ± 6.0 (N = 88) df 1,125 F = 3.709 p = 0.056 Post-traumatic stress disorder 23 36.3 ± 6.1 3.9 ± 1.0 (N = 26) df 1,91 F = 1.388 p = 0.243 Simple phobia 28 35.8 ± 6.1 2.5 ± 2.4 (N = 54) df 1,66 F = 10.016 p = 0.002 Agoraphobia 24 35. psychosocial disability. Therefore, these elements are not negligible on a clinical level.…”
Section: Discussionmentioning
confidence: 99%
“…For each person with GAD, a cell was created including all the people without GAD in the database of the same age and gender, thus four people for each cell were selected. The burden in impairing of HR-QoL attributable to GAD was also compared to a similar measure obtained to other diseases in previous case-control studies, which were carried out with the same methodology [45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The findings are consistent with other studies that had seen the co-morbid agoraphobic component affecting the quality of life in a measure not inconsistent with other anxiety disorders [ 36 , 37 ]. Similarly, the impact on quality of life of obsessive-compulsive disorder was found to be influenced by the co-morbidity with bipolar spectrum disorders [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Similarly, the impact on quality of life of obsessive-compulsive disorder was found to be influenced by the co-morbidity with bipolar spectrum disorders. 38 However, the attributable burden of agoraphobia is nonnegligible. When compared to the attributable burden of other chronic and disabling conditions in studies that applied the same methodology of this study, the attributable burden of agoraphobia resulted higher than the attributable found in celiac disease, 39 lower than in multiple sclerosis, 40 or in fibromyalgia, 41 but comparable to the one observed for Wilson disease and eating disorders.…”
Section: Discussionmentioning
confidence: 99%